A Systematic Literature Review of Critical Leadership: Power Dynamics, Social Justice, and Transformative Practices in Organizational Contexts - Muhammad Ifan Fadillah; Budi Santoso; Rio Nardo (CAKRAWALA : Management Science Journal, 2025)
This systematic literature review critically synthesizes the expanding body of scholarship on critical leadership, focusing on power dynamics, ideological critique, social justice, and transformative practices within organizational and community contexts. Moving beyond traditional leadership paradigms that emphasize individual traits and hierarchical effectiveness, critical leadership theory interrogates leadership as a contested socio-political process embedded in structures of power and domination. This review maps key theoretical frameworks, methodological trends, and empirical applications spanning indigenous governance, educational reform, grassroots activism, and corporate sustainability. The analysis reveals enduring tensions between transformative aspirations and institutional constraints, highlighting the complex interplay of identity, discourse, and collective agency. Notably, the review identifies significant gaps in geographic representation, methodological pluralism, and thematic coverage, particularly in crisis leadership, media discourse, and intersectional minority experiences. Emerging opportunities call for integrative, context-sensitive, and interdisciplinary approaches that enhance critical leadership’s capacity to address systemic inequities and foster emancipatory social change. By offering a comprehensive synthesis of conceptual, empirical, and methodological insights, this review advances theoretical clarity and practical relevance, positioning critical leadership as a vital framework for ethical and socially responsive leadership in an increasingly complex global landscape.